Availability of Infrastructure Facilities and Teacher Competence on the Sustainability of the Implementation of the State Vocational School Learning Process in Palembang City - Iskandar Iskandar; Edi Harapan; Syaiful Eddy (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research aims to analyze the influence of the availability of infrastructure and teacher competence on the sustainability of the implementation of the learning process at State Vocational Schools in Palembang City. The availability of adequate infrastructure and high teacher competency is believed to have an important role in improving the quality of learning and the effectiveness of the teaching and learning process in schools. The method used in this research is a quantitative approach with survey techniques, involving a sample of teachers and school principals from several state vocational schools in Palembang City. Data was collected through a questionnaire which was processed using regression analysis to test the relationship between the two independent variables and the continuity of learning. The research results show that both the availability of infrastructure and teacher competence have a significant effect on the smoothness and success of the learning process at State Vocational Schools in Palembang City. Thus, efforts to improve infrastructure and increase teacher competency are important factors in improving the quality of education at the vocational school level.